Variation entry of sediment, organic matter and different forms of phosphorus and nitrogen in flood and normal events in the Anzali wetland. Issue 2 (9th December 2021) - Ebrahimi, Eisa; Asadi, Hossein; Joudi, Mehrnosh; Rashti, Mehran Rezaei; Farhangi, Mohammad Bagher; Ashrafzadeh, Afshin; Khodadadi, Maral
Abstract: Phosphorus (P), nitrogen (N) and organic component are released from the soil into surface bodies by runoff and erosion, causing the pollution and eutrophication of water resources. This study aimed to investigate the seasonal changes in loads of N and P components, and organic matter (OM) in the Pasikhan River in flood and normal conditions. Sampling was performed monthly during normal flow conditions and for five flood events. The concentrations of P and N components were measured in the samples. The OM of the suspended sediments was determined by the combustion method. Under the normal flows, the maximum loads of total P and OM were about 0.553 mg l −1 (STD = 0.11) (November) and 3.41% (STD = 1.17) (November) in the autumn, respectively. The total N concentration of 0.533 mg l −1 (STD = 0.12) was observed in the winter. In the flood events, the TP, TN and OM ranged from 0.48 to 3.5 mg l −1, 0.28 to 0.79 mg l −1 and 1.24 to 4.11%, respectively. The results indicated a high risk of eutrophication in the Pasikhan River. Also, the study revealed that in a severe flood event, some 113.9 tons h −1 of OM can be released from the river watershed. Furthermore, there was a high correlation between the amount of P and OM losses with the concentration of suspended sediments in different flood events. Finally, it is concluded that if the floods are not controlled, they not only cause a rapid loss of soil nutrients and OM but also lead to severe eutrophication in the Anzali wetland. HIGHLIGHTS: The Pasikhan River is at risk of eutrophication. Time, flow rate and area are the most important determinants of pollution. Nitrogen and phosphorus losses are the highest in autumn and winter. Graphical Abstract